A systematic review and meta‐analysis of asthma outcomes following endoscopic sinus surgery for chronic rhinosinusitis. Issue 10 (1st July 2013) - Vashishta, Rishi; Soler, Zachary M.; Nguyen, Shaun A.; Schlosser, Rodney J.
Abstract : Background: Patients suffering from both chronic rhinosinusitis (CRS) and asthma demonstrate improved asthma outcomes when upper airway inflammation is controlled with medications. It is unclear if similar benefits exist when the upper airway is treated surgically. This study presents a systematic review and meta‐analysis to assess the effects of endoscopic sinus surgery (ESS) on asthma outcomes. Methods: Ovid MEDLINE and the Cochrane databases were searched to identify studies examining asthma outcomes in patients with CRS following ESS. Included studies involved a cohort of at least 5 patients and reported at least 1 postoperative asthma outcome. Results: Twenty‐two studies involving a total of 891 patients were identified. Mean follow‐up across all studies was 26.4 months. Patients reported improved overall asthma control in 76.1% (95% confidence interval [CI], 71.9% to 80.3%) of cases. The frequency of asthma attacks decreased in 84.8% (95% CI, 76.6% to 93.0%) of patients and the number of hospitalizations decreased in 64.4% (95% CI, 53.3% to 75.6%). Decreased use of oral corticosteroids was seen in 72.8% (95% CI, 67.5% to 78.1%) of patients; inhaled corticosteroid use decreased in 28.5% (95% CI, 22.6% to 34.5%) and bronchodilator use decreased in 36.3% (95% CI, 28.9% to 43.7%) of patients. Mean improvement in predicted forced expiratory volume at 1 second (FEV1 ) was 1.62%, but was not statistically significant ( p = 0.877). Conclusion: ESS in patients with concomitant bronchial asthma improves clinical asthma outcome measures, but not lung function testing. Difficulty conducting controlled clinical trials of ESS limits the strength of conclusions which can be reached.